Road to Net Zero Strategic Pathways for Sustainability-Driven Business Transformation - Zipse, Oliver; Hornegger, Joachim; Becker, Thomas; Beckmann, Markus; Bengsch, Michael; Feige, Irene; Schober, Markus (Springer International Publishing : Imprint: Springer, 2023)
With this open access book, delve into the insights of respected leaders from academia and industry as they unravel the intricacies of sustainability-driven business transformation. This meticulously curated edited volume reflects on The Road To Net Zero, underscoring the need for pioneering pathways. Embark on a collaborative learning journey and explore key issues along the road to transformation, such as crafting corporate sustainability strategies, new forms of corporate disclosure, transforming value chains, and harnessing the power of technological innovation. Packed with guiding questions and distilled findings from research, this book is a must-read for all decision-makers, strategists, engaged citizens, educators, and learners committed to driving change and shaping a more sustainable future.